2007
DOI: 10.1002/jgm.1106
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus‐mediated interleukin‐13 gene therapy attenuates acute kidney allograft injury

Abstract: This study demonstrates that IL-13 gene therapy in the graft significantly attenuates acute renal allograft damage, suggesting local therapy with IL-13 as a strategy to reduce the need for systemic immunosuppressive medication and thereby its side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…On the other hand, as cell proliferation is integral to recovery of tubular damage, IL-13 may limit the extent of the injury, promoting replacement of dead and apoptotic cells, and thus slowing graft deterioration. The later is in concordance with recent studies by Sandovici et al [14], which indicate that IL-13 gene therapy of kidney graft could attenuate acute allograft rejection, a phenomenon for which IL-13 driven PTEC proliferation may support. Experiments such as depletion of IL-13 in vivo using antibodies [6] or chimeric protein [34] could provide clues towards determining the exact role played by this cytokine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, as cell proliferation is integral to recovery of tubular damage, IL-13 may limit the extent of the injury, promoting replacement of dead and apoptotic cells, and thus slowing graft deterioration. The later is in concordance with recent studies by Sandovici et al [14], which indicate that IL-13 gene therapy of kidney graft could attenuate acute allograft rejection, a phenomenon for which IL-13 driven PTEC proliferation may support. Experiments such as depletion of IL-13 in vivo using antibodies [6] or chimeric protein [34] could provide clues towards determining the exact role played by this cytokine.…”
Section: Discussionsupporting
confidence: 92%
“…IL-13 also induces the production of transforming growth factor beta (TGF ) in macrophages, indirectly promoting fibrosis [13]. On the other hand, IL-13 was recently described to have a protecting role against acute rejection, as graft receiving IL-13 gene therapy showed a lower rate of injury [14].…”
Section: Introductionmentioning
confidence: 99%
“…The infiltrating cells include macrophages and cytotoxic T cells, which increase the levels of E-selectin, TNF-␣, and IFN-␥, resulting in renal dysfunction and apoptosis (17,35). TNF-␣ production is triggered by locally produced reactive oxygen species (ROS), as well as by I/R injury, which activate transcription factor NF-B and cause renal dysfunc- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that enhancing Th2 immunity with exogenous IL-4 and/or IL-10 and IL-13 reduced renal injury in a model of experimental immune-mediated GN. 16,17,20 Thus, the protective effect of IL-25 in this study could be caused by its induction of Th2 responses.…”
Section: Discussionmentioning
confidence: 99%
“…16 An adenovirus expressing IL-13 injected into kidney also increases renal IL-13 levels and attenuates acute kidney allograft injury. 17 These studies have suggested that enhancing Th2 responses in kidney may reduce renal inflammation and renal damage. Therefore, given its ability to induce Th2 immune responses and to inhibit macrophage-derived inflammatory cytokines, IL-25 is a potential candidate for treating kidney disease.…”
mentioning
confidence: 99%